Association between maternal gestation weight gain and preterm birth according to pre-pregnancy body mass index and HbA1c - Xiaoxiao Zhang; Binbin Yin; Kaiqi Wu; Lei Fang; Yan Chen (Journal of Obstetrics and Gynaecology)
Background To investigate the association between gestational weight gain (GWG) and preterm birth (PTB) according to pre-pregnancy body mass index (pp-BMI) and glycated haemoglobin (HbA1c) within the normal range.Methods We conducted a population-based retrospective cohort study between July 2017 and January 2020 at Women’s Hospital, Zhejiang University School of Medicine. Women were classified into three groups (inadequate GWG, appropriate GWG, and excessive GWG). In addition, women were divided into different subgroups according to pp-BMI and HbA1c. We estimated the odds ratios (OR) with 95% confidence intervals (CI) to assess the associations between GWG and the risk of PTB. Meanwhile, we adjusted for possible confounding factors, including maternal age, infant sex, family history of diabetes, education, pregnancy mode, delivery mode, parity, and gravidity.Results The study involved 23,699 pregnant women, of which 1124 (4.70%) were PTB. Women who had inadequate GWG were found to have a significantly higher risk of PTB compared to women with appropriate GWG. In contrast, women with excessive GWG had a reduced risk of PTB. Similarly, GWG and PTB had similar risk associations in the HbA1c and pp-BMI subgroups. Among women with pp-BMI <18.5 kg/m2, women with inadequate GWG had a significantly increased risk of PTB compared with women in the control group (HbA1c 4.6–5.0%, appropriate GWG), and the risk increased with increasing HbA1c levels. Similar results were observed in women with normal pp-BMI.Conclusions There was a significant association between GWG and the risk of PTB, but the risk varied by pp-BMI and HbA1c levels. Reasonable weight gain during pregnancy is essential to prevent PTB. Furthermore, while HbA1c is within the normal range, the higher levels should be noticed.